The Moderating Role of Religiosity in the Relationship Between Machiavellianism and Tax Avoidance - Muhammad Nugraha; Rina Apriliani; IIP Dyah Kusumaningati; Umi Mas'ulah; Jenni Veronika Br Ginting (Lembaga Riset dan Inovasi Al-Matani, 2025)
Tax avoidance can be carried out by taxpayers themselves or with the assistance of tax consultants, so tax consultants play a crucial role in facilitating this action. The purpose of this study is to analyze the nature of Machiavellianism on tax avoidance, with religiosity as a moderating variable. The study used a survey of corporate taxpayers in Jakarta. Corporate taxpayers were chosen because, in terms of total Indonesian state revenue, corporate taxpayers contribute significantly more than individual taxpayers. Hypothesis testing used regression analysis with the help of the SmartPLS program. Based on the research findings, Machiavellianism partially influences tax avoidance in Jakarta. On the other hand, the religiosity variable is able to moderate the effect of Machiavellianism on tax avoidance.